Strengthening Small And Medium Enterprises (SMEs) Through Sociopreunership-Based Communities In Technology Sustainability - Martin Purnama Chandra (Administrasi Bisnis Indonesia, 2022)
The low percentage of digitization implementation is the biggest challenge in growing digital technology among Small and Medium Enterprises (SMEs). The limited level of education has implications for how to learn and understand everything of digitalization, so support is needed in optimizing the use of technology in Sociopreneurship-based communities. This research aims to explain the strengthening of SMEs through Sociopreneurship-based communities to achieve technology sustainability. The method used is descriptive qualitative with primary and secondary data sources. The result of this research is that the community-based Sociopreneurship plays a role in accommodating the private and government sectors to overcome the barriers to using technology that is often faced by SMEs. With the idea that technology can add value to this sector, the existence of a community will lead to an analysis of how technology changes SMEs in running their business and creates a competitive advantage. They also collaborate with universities for implementation, experimentation, and discoveries on the practice of using technology in the SMEs sector, which will be poured into the research, which will then be evaluated and applied. This research concludes that Sociopreneurship-based communities are an important factor in strengthening SMEs in achieving technology sustainability. Sociopreneurship between various related parties provides support in the use of digital technology to create competitiveness and competitive advantage as an intangible innovation capability.